2014
DOI: 10.1097/jtn.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Rehabilitation Cost Following Intensive Care Unit Stay in Multiple Trauma Patients

Abstract: Severely injured victims of motor vehicle crashes suffer from serious problems in terms of HRQOL which is gradually improved even 2 years after hospital discharge. In addition, HRQOL is significantly related to income. Resources used for rehabilitation decrease over time, but even at 24 months, the patients still use half of the amount as compared with the cost of the first 6 months after trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 25 publications
0
24
2
Order By: Relevance
“…This significant drop and rapid improvement in physical function and more moderate reduction and improvement in mental health is consistent with that reported in some trauma ICU cohorts in other countries (18,48) although there are occasional reports in conflict with this. In a Greek cohort of 85 patients using the EQ-5D severe problems of anxiety were reported in a greater proportion of patients, with more than 60% of patients reporting severe anxiety 6 months after injury, with similar problems in mobility and self-care (46). Follow-up interviews in this Greek study were all conducted in person and this may have influenced the higher levels of compromise in comparison to the current study where self-report was used, although previous examination of the effect of data collection method has found clinical interview resulted in less compromised, rather than more compromised, quality of life results when compared to selfreport (49).…”
Section: Discussionmentioning
confidence: 99%
“…This significant drop and rapid improvement in physical function and more moderate reduction and improvement in mental health is consistent with that reported in some trauma ICU cohorts in other countries (18,48) although there are occasional reports in conflict with this. In a Greek cohort of 85 patients using the EQ-5D severe problems of anxiety were reported in a greater proportion of patients, with more than 60% of patients reporting severe anxiety 6 months after injury, with similar problems in mobility and self-care (46). Follow-up interviews in this Greek study were all conducted in person and this may have influenced the higher levels of compromise in comparison to the current study where self-report was used, although previous examination of the effect of data collection method has found clinical interview resulted in less compromised, rather than more compromised, quality of life results when compared to selfreport (49).…”
Section: Discussionmentioning
confidence: 99%
“…7(p822) Patients' ability to use rehabilitation is an important predictor of long-term outcomes of care. [2][3][4]7 Nevertheless, despite its known benefits, rehabilitation may not be available to all patients. 8,9 Studies have demonstrated strong associations between insurance coverage and rehabilitation use 8,[10][11][12] as well as between a lack of insurance and fatal outcomes, including in-hospital mortality [13][14][15] and failure to rescue (FTR).…”
mentioning
confidence: 99%
“…Assessment of the functional status of polytrauma patients is particularly challenging due to the large range of types and severity of injuries. The functional status of trauma survivors has been inferred in health-related quality of life (HRQOL) studies in this population, as in studies conducted in Spain 17 ) and Greece 18 ) . At three months post injury, severe trauma victims show drastically reduced functionality and HRQOL 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…At six months, trauma victims still show a deteriorated HRQOL; although improvement may be observed at 12 months, complete recovery of previous condition is not obtained 17 ) . For injured victims of motor vehicle crashes, serious problems in terms of HRQOL gradually improve during the 2 years after hospital discharge 18 ) .…”
Section: Introductionmentioning
confidence: 99%